Evolution Mechanism of Interconnected Vertical Fractures in the Overburden of Longwall Coal Mining - He Changchun; Lu Weiyong; Zha Wenhua (Geofluids)
Whether a tensile failure fracture will penetrate a stratum is difficult to ascertain at present. In view of this, the method of similar simulation and field verification are used to carry out a systematic study. Similar simulations show that tensile failure fractures will penetrate the layered strata if the compressive stress is greater than the compressive strength. Theoretical analysis points out that whether the tensile failure fractures will penetrate the layered strata can be expressed by the value of criterion of interconnected vertical fractures and the compression-tension ratio. When the value of criterion of interconnected vertical fractures is greater than the compression-tension ratio, the layered strata will break. This criterion was qualitatively verified with a field test. The results of this paper are of great significance for the prevention of water inrush in coal mines, and it can also promote the understanding of the law of strata movement.